Gestão da produção aplicada à confecção de peças de vidro pré-fabricadas na cidade de Abaetetuba – PA - PINHEIRO, Arthur Brito (2022)
The present study was carried out in a glass shop located in the municipality of Abaetetuba - Pará, specifically in the sector of making prefabricated glass pieces. The objective of this work is to identify operational obstacles in the production process that reflect negatively on the production capacity of the glassworks and that therefore can be improved, from this identification, a study of methods was carried out to define the times and processes in four operations observed and thus pointing out the existing bottlenecks in production. At the beginning of the study, the company's production process was mapped, then samples of process times were collected for three days and the routine of employees was also observed in order to verify how they perform their tasks, also analyzing the ergonomic conditions provided in the work environment in question. Finally, with the results obtained, it was possible to analyze the observed reality in more detail, proposing suggestions for improvements that become relevant for the enterprise in order to find solutions to the problems identified and, in this way, open the way for the improvement of its productive chain.